Critical Connections: The Importance of Community-Based Organizations and Social Capital to Credit Access for Low-Wealth Entrepreneurs. (May 2014) - Casey, Colleen
This article studies the relationship between linking social capital and credit access for low-wealth entrepreneurs. I argue that the support provided by community-based organizations facilitates critical linkages to credit access for low-wealth entrepreneurs. Data on nascent firms engaging in start-up efforts in the United States in 2005 from the Panel Survey of Entrepreneurial Dynamics II (PSED II) are used to test the effects of government, bank, and community-based organization supports. The results suggest that government support has a positive effect for entrepreneurs overall. However, among low-wealth entrepreneurs, support provided by community-based organizations significantly increases access to credit for start-up activities.